The strength of multi-scale modeling to unveil the complexity of radical polymerization - D’hooge, Dagmar R.; Van Steenberge, Paul H.M.; Reyniers, Marie-Françoise; Marin, Guy B. (Progress in polymer science, 2016)
The strength of multi-scale modeling to support the fundamental understanding and design of radical polymerization processes is illustrated, considering both controlled and free radical polymerization (CRP/FRP) in non-dispersed (bulk/solution) and dispersed (suspension/emulsion) media. At the molecular scale, the importance of joint experimental and theoretical studies is highlighted. At the micro-scale, the concept of apparent rate coefficients is elaborated to account for the possible influence of diffusional limitations on the local reaction rates. At the meso-scale, the key characteristics to fundamentally describe the evolution of the particle size distribution are covered and the possible interaction with the micro- and macro-scale is discussed. At the macro-scale, the main mathematical tools to assess the relevance of mixing and temperature gradients are provided. Several examples on CRP and FRP processes are included to showcase the modeling capabilities for each scale, focusing both on laboratory and industrial reactors.